Nitrogen and potassium fertilization on ‘Caipira’ and ‘BRS Princesa’ bananas in the Ribeira Valley - Edson S. Nomura; Francine L. Cuquel; Erval R. Damatto Junior; Eduardo J. Fuzitani; Ana L. Borges; Luis A. Saes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT ‘BRS Princesa’ (AAAB) and ‘Caipira’ (AAA) banana cultivars have similar sensorial features in comparison to the ‘Maçã’ banana. They are resistant to Panama disease, which allows them to grow in the Ribeira Valley, the largest banana plantation area in the São Paulo State. However, there is no information on how to fertilize crop under these edaphoclimatic conditions. This study aimed to evaluate the development and production of ‘Caipira’ and ‘BRS Princesa’ bananas, by applying four fertilization doses of N and K2O (no fertilization; 175 and 285 kg ha-1 year-1; 350 and 570 kg ha-1 year-1; 525 and 855 kg ha-1 year-1). The most adequate fertilizer recommendation for ‘Caipira’ and ‘BRS Princesa’ cultivars was 150% of the standard recommendation for banana (525 kg ha-1 year-1 of N and 855 kg ha-1 year-1 of K2O) in both production cycles, promoting adequate growth and production, since most of the evaluated characteristics showed linear responses with the increase in the fertilization doses. ‘Caipira’ and ‘BRS Princesa’ require higher amounts of N and K than that recommended for the banana crop in the São Paulo State, in order to express their productive potential.